Multi-scale modelling of heterogeneous shell structures - Massart, T.J.; Mercatoris, B.C.N.; Piezel, B.; Berke, P.; Laiarinandrasana, L.; Thionnet, A. (Computer Assisted Methods in Engineering and Science, 2017)
This paper reviews multi-scale computational homogenisation frameworks for the non-linear behaviour of heterogeneous thin planar shells. Based on a review of some of the currently available methods, a computational homogenisation scheme for shells is applied on to representative volume elements for plain weave composites. The effect of flexural loading on the potential failure modes of such materials is analysed, focusing on the reinforcement-matrix delamination mechanism. The attention is next shifted toward failure localisation in masonry unit cells. Subsequently, a recently developed computational FE 2 solution scheme accounting for damage localisation at structural scales based on RVE computations is applied.